2017
DOI: 10.1264/jsme2.me16159
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Biodiversity of Halophilic Microorganisms on Historic Masonry Buildings

Abstract: The aim of the present study was to obtain insights into the relationship between the chemical (salt content and pH) and physico-mechanical (humidity and compressive strength) properties of mineral-based materials from historic buildings with salt efflorescence and the growth and biodiversity of halophilic microorganisms. Samples were mainly characterized by pH 6.5-8.5 and a moisture content of between 0.12 and 3.3%. Significant variations were also found in the salt content (sulfates, chlorides, and nitrates)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Each crevice and intergrain space can become a salty micro-niche available for specialized microorganisms; along with the salt physical action, the selected community can contribute to stone structural destabilization [73][74][75][76]. The exclusive isolation of the halophilic fungi from sand disaggregated monuments only, highlighted as salt-attacked monuments constitute a suitable habitat for selected osmophilic/osmotolerant microorganisms [75,77,78]. However, this phenomenon seems to be progressive since Neoph.…”
Section: Marble Deterioration Degree Selects the Resident Fungal Comm...mentioning
confidence: 99%
“…Each crevice and intergrain space can become a salty micro-niche available for specialized microorganisms; along with the salt physical action, the selected community can contribute to stone structural destabilization [73][74][75][76]. The exclusive isolation of the halophilic fungi from sand disaggregated monuments only, highlighted as salt-attacked monuments constitute a suitable habitat for selected osmophilic/osmotolerant microorganisms [75,77,78]. However, this phenomenon seems to be progressive since Neoph.…”
Section: Marble Deterioration Degree Selects the Resident Fungal Comm...mentioning
confidence: 99%
“…Curiously, members of the Rubrobacteria class were only detected in a relatively high proportion (23% of the phylum Actinobacteria) in S3, where it was possible to identify only the genus Rubrobacter. Unfortunately, it was not possible to infer at the species level, but species of this genus have been widely detected in terrestrial habitats, as stone monuments usually subjected to salt weathering (Otlewska et al 2017) as well as in marine environments, and some of them are known to be halotolerant, thermotolerant, and radiotolerant (Egas et al 2014).…”
Section: Prokaryotic Communitymentioning
confidence: 99%
“…However, for the consistency of the bacterial amplicon analysis they were filtered out. Nevertheless, this result showed that halophilic microorganisms are abundant on the surfaces of masonry and mortar and should also be carefully studied as they can contribute to the deterioration of historic buildings [52].…”
Section: Discussionmentioning
confidence: 99%